2013
DOI: 10.2147/nss.s38369
|View full text |Cite
|
Sign up to set email alerts
|

Estimating adolescent sleep patterns: parent reports versus adolescent self-report surveys, sleep diaries, and actigraphy

Abstract: BackgroundIn research and clinical contexts, parent reports are often used to gain information about the sleep patterns of their adolescents; however, the degree of concordance between parent reports and adolescent-derived measures is unclear. The present study compares parent estimates of adolescent sleep patterns with adolescent self-reports from surveys and sleep diaries, together with actigraphy.MethodsA total of 308 adolescents (59% male) aged 13–17 years completed a school sleep habits survey during clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 18 publications
7
88
0
2
Order By: Relevance
“…Although previous research points toward higher endorsement of sleep problems by parents relative to their anxious children, some methodological differences are noteworthy. In the current study we attempted to ensure that both parent and child reports of sleep problems tapped the same behavioral domains, using the same rating format, and number of items whereas prior studies have tended to rely on non-parallel measures of sleep problems (Chase and Pincus 2011;Short et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous research points toward higher endorsement of sleep problems by parents relative to their anxious children, some methodological differences are noteworthy. In the current study we attempted to ensure that both parent and child reports of sleep problems tapped the same behavioral domains, using the same rating format, and number of items whereas prior studies have tended to rely on non-parallel measures of sleep problems (Chase and Pincus 2011;Short et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between child reports and actigraphy reveal a similarly discrepant pattern and child-reported sleep problems such as prolonged sleep onset are often not corroborated by parents (Arora et al 2013;Short et al 2012). For example, Short et al (2013) found parents reported greater total sleep duration on both weekdays and weekends compared to adolescent reports and actigraphy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, they were three-times more likely to engage in self-harming behaviors(OR=3.0, 95% CI: 1.1-7.9, p=0.03).Adolescents treated with other sleep medications (such as antihistamines and non-benzodiazepines) did not fare much better and still had greater likelihood of self-harming behavior [90].…”
Section: Trazodonementioning
confidence: 98%
“…Az adatokat önbevallásos kérdőívből nyertük, adatainkból a szubjektív alvásidő megítélésére van lehetőség. Ez a módszer a gyermekek alvásmintázatáról a szülői kérdő-íveknél pontosabb, az objektív műszeres eljárásoknál azonban kevésbé megbízható képet ad [31]. A két ország adatainak összehasonlítását korlátozza a rendelkezésre álló két minta eltérő nagysága, az eltérő átlagéletkor, illetve iskolatípusok.…”
Section: Megbeszélésunclassified